Valorization of potato peel: a biorefinery approach - Pathak, P. D.; Mandavgane, S. A.; Puranik, N. M.; Jambhulkar, S. J; Kulkarni, B. D. (Critical Reviews in Biotechnology, 2017)
Potato is the fourth main crop consumed worldwide and is an important constituent in the human diet. Consequently, potato is widely used in food-processing industries. However, these industries generate massive amounts of potato peel (PP) as a by-product, which is usually considered a waste, and is discarded. Interestingly, recent research suggests that PP is a valuable source of bioactive compounds, which can be converted into value-added products. In this study, we review the physicochemical composition and valorization of PP. In addition to being used as a dietary fiber or medicine, the value-added products obtained by the fermentation of PP have multiple uses, including their use as adsorbents, biocomposites and packaging materials. These products can also be used in energy production, biopolymer film development, corrosion inhibition and the synthesis of cellulose nanocrystals. The biorefinery approach for PP will increase the value of this waste by producing an array of value-added products and reducing extensive waste generation.
Keywords: Bioactive compounds; Biorefinery; Potato peel; Valorization; Value-added products

Waste to wealth: a Case study of papaya peel - Pathak, Pranav D. (Waste and Biomass Valorization, 2019)
Papaya is a popular fruit consumed worldwide and well-known for its food and nutritional values. It is used in food industries for the production of jams, jellies, etc. As a result, these industries generate huge amounts of papaya peel (PP) and seeds as by-products, which are typically considered a waste, and thus discarded. However, our current investigation indicates that PP is a valuable source of bioactive compounds, which can be converted into many value-added products. In this article, we review the physicochemical composition and valorization of PP. PP can be utilized to obtain many value-added products by fermentation (e.g., biofuels, adsorbents, dietary fibers, biomedicine, biomaterials). The biorefinery approach for PP will definitely increase the value of this waste by producing an array of value-added products and achieving zero waste generation.
Keywords: Bioactive compounds; Biorefinery; Papaya peel; Valorization; Value-added products